The Influence of Job Stress and Workload on Employee Work Motivation - Yuliastanty, Susi; Putra, Amal Razaly (UPI YPTK Journal of Business and Economics, 2024)
Work motivation is the basis for an organization to develop itself, both in government and private agencies. The objectives of the research are as follows: (1) The partial influence of work stress on the work motivation of employees at the West Padang District Head Office, Padang City. (2) The partial influence of workload on the work motivation of employees at the West Padang District Head Office, Padang City. (3) The influence of work stress and workload simultaneously on the work motivation of employees of the West Padang District Head Office, Padang City. Data collection methods are Field Research and Library Research. Types and sources of data are primary data and secondary data. The population in this study consisted of all employees of the West Padang Subdistrict Office, namely 37 people and a sample of 37 people. The analysis method uses multiple linear regression analysis. The results of the research found that (1) work stress partially has a significant effect on the work motivation of employees at the West Padang District Head Office, Padang City. (2) work workload partially has a significant effect on the work motivation of employees of the West Padang District Head Office, Padang City; (3) the value of the coefficient of determination to the work motivation of employees at the West Padang District Head Office, Padang City is shown by the Adjust R Square value of 0847, this means the large contribution to work stress and workloadtoWork motivation of employees at the West Padang District Head Office, Padang City is 84.7% while the rest is influenced by other variables outside this research such as work discipline, work environment, compensation and others.